EFEKTIVITAS PEMBERDAYAAN KELOMPOK PENGOLAHAN HASIL PERIKANAN DI KOTA BANJARMASIN - Muhammad Riduansyah Syafari; Trisylvana Azwari; Siti Juwairiyah (Jurnal PubBis, 2020)
This research was conducted to determine the effectiveness of the empowerment of fisheries product processing groups in Banjarmasin using a qualitative approach. The data analysis technique uses the interactive analysis model of Miles and Huberman with 3 stages of analysis, consisting of data reduction, data display, and verification / conclusion drawing. The results showed that the effectiveness of the empowerment of fisheries product processing groups in Banjarmasin City that was focused in East Banjarmasin District was not yet effective. This is based on the group formation program based on the potential of raw materials, so this goal has been carried out in accordance with the needs of the group, but sometimes it is hampered by seasons which result in the scarcity of raw materials. Based on the concept of environmental carrying capacity, for fishery raw material needs is very large, that is, it is close to large and medium rivers, and is passed through by many kelotok sellers of raw fisheries caught in both fresh and marine fisheries. However, the carrying capacity of this environment has not been matched by the work ethic of group members in groups and prefers to cultivate individually, and is not supported by good managerial and administrative groups (poor managerial and administrative). The effectiveness constraints consist of three; 1) Characteristics of Group Organizations that are still weak, 2) Characteristics of a good environment, but the potential of the wet environment has not been utilized properly, 3) Characteristics of group members tend to be individual. Keywords: Effectiveness, Empowerment, Group